PRELIMINARY STUDY OF ELEMENTARY SCHOOL STUDENTS' LEARNING NEEDS IN STEM EDUCATION: A CONSTRUCTIVISM AND MULTICULTURALISM PERSPECTIVE - Dewi, Nastitisari; Marini, Arita; Maksum, Arifin; Nurhasanah, Nina; Zakiah, Linda (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
This preliminary study investigates the learning needs of elementary students and teacher perceptions regarding STEM education in schools where it has not yet been implemented at Sukabumi Data were collected from 127 students and 15 teachers in elementary schools at Sukabumi City through questionnaires and semi structured interviews. The results indicate that a majority of students prefer experiment-based learning (41,73% strongly agree, 40,16% agree) and technology integration (38,38% strongly agree, 42,5% agree), with notable support for project- based learning and group collaboration. In contrast, teachers identified significant callenges in implementing STEM education, including limited acces to essential tools and technology, inadequate infastructure (60% strongly agree), and insufficient training (46,67% strongly agree). The findings suggest that, despite strong student interest in STEM learning, effective implementation requires enhanced support and resources. There is a clear need for ongoing professional development for teachers to facilitate innovative and collaborative learning processes. This study underscores the importance of futher research and initiatives to support STEM education in elementary schools, ensuring that both students and teachers are adequately equipped for successful learning experiences.